Rekomendasi Content Creator Terbaik sebagai Pendukung Keputusan Penilaian pada Agensi Menggunakan Metode TOPSIS - Eugenius Kau Suni; Stephen Aprius Sutresno (Building of Informatics, Technology and Science (BITS), 2023)
As an agency, it is necessary to evaluate and assign value to the content outcomes that have been published by content creators periodically. Aurora News Agency, which is one of the content creator agencies for Snack Video, has over 700 member content creators. This requires specialized techniques to facilitate and expedite the assessment of the performance of these content creators. Therefore, research was conducted on a decision support system using the TOPSIS method as a decision-making tool for evaluating the best content creators within the agency. Data was collected from a total of 630 content creators, and after undergoing data cleansing processes, a total of 10,916 content items were obtained. The research results present a ranking of the top 10 content creators based on their preference scores, ranging from the highest to the lowest. Anemz Tv is the content creator with the highest preference score of 0.4368, securing the first rank. On the other hand, Talenta.TV is the content creator with a preference score of 0.3203, earning the second rank. Upon analysis, differences in strategies for each content creator became apparent, with some focusing on quantity and others placing emphasis on the quality of content. In conclusion, the application of the TOPSIS method can be implemented relatively simply, with sufficiently fast computations, and it yields a diverse range of preference scores